Baptisan Roh Kudus yang Alkitabiah: Upaya Menjawab Perbedaan Pendapat di Kalangan Denominasi Gereja - Daniel Setiawan Giamulia; Sugiono Sugiono (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
The aim of writing in this scientific journal is to obtain a comprehensive picture of the Biblical baptism of the Holy Spirit. The term baptism in the Holy Spirit is not a new term for churches, especially for Pentecostal churches. Understandings of the teachings of the baptism of the Holy Spirit are very diverse. Each church has a different dogma. This resulted in quite a lot of division among believers. These differences in views and opinions became the impetus for the author to investigate the Bible data regarding Spirit baptism. The research method used is descriptive qualitative with a literature study approach and inductive interpretation. The result obtained is that the baptism of the Holy Spirit has the meaning of entering believers into the Body of Christ. Jesus Christ who baptized the Holy Spirit. There are two ways in which the baptism of the Holy Spirit occurs, namely without the laying on of hands and with the laying on of hands. The result of the baptism in the Holy Spirit is receiving the gift of the Holy Spirit, becoming a member of the Body of Christ and becoming one in the death, burial and resurrection of Christ.AbstrakTujuan penulisan dalam jurnal ilmiah ini ialah bermaksud untuk mendapatkan gambaran yang komprehensif mengenai baptisan Roh Kudus yang Alkitabiah. Istilah baptisan Roh Kudus bukan merupakan istilah yang baru bagi Gereja-gereja khususnya bagi Gereja beraliran Pentakosta. Pemahaman tentang ajaran baptisan Roh Kudus begitu beragam. Setiap gereja memiliki dogma yang berbeda. Hal ini mengakibatkan cukup banyak perpecahan di antara orang-orang percaya. Perbedaan pandangan dan pendapat tersebut menjadi dorongan untuk penulis menyelidiki data-data Alkitab mengenai baptisan Roh. Metode penelitian yang dipakai adalah kualitatif deskriptif dengan pendekatan studi pustaka dan Tafsiran Induktif. Hasil yang diperoleh ialah Baptisan Roh Kudus memiliki pengertian yakni memasukkan orang percaya kedalam Tubuh Kristus. Yesus Kristus yang membaptis Roh Kudus. Cara terjadinya baptisan Roh Kudus ada dua yaitu tanpa penumpangan tangan dan dengan penumpangan tangan. Akibat dari baptisan Roh Kudus menerima karunia Roh Kudus, menja dianggota Tubuh Kristus dan menjadi satu dalam kematian, penguburan dan kebangkitan Kristus.